The Effect of Group Communication on Social Concern: A Study of Creative Surau Community in Nagari Limo Kaum - Fitri Roihanah Nasution; Oktri Permata Lani (KINEMA: Jurnal Komunikasi dan Penyiaran, 2026)
This study examines the effect of group communication within the Creative Surau Community on social concern among residents of Nagari Limo Kaum, West Sumatra, Indonesia. The Creative Surau Community, established in 2023, has grown from 8 to over 80 members and received formal recognition from the Regional Cultural Preservation Center (BPK) of West Sumatra. Despite its visible social impact, no prior quantitative study had measured the extent to which its group communication influences community social concern. This study employed a quantitative descriptive approach with simple random sampling. The population comprised 700 residents aged 16–18 years across eight sub-villages (jorong); 88 respondents were selected using Slovin’s formula. Data were collected via a structured four-point Likert-scale questionnaire and analyzed using Spearman’s rank correlation following confirmed non-normal data distribution. Results revealed a strong, statistically significant positive correlation (rₛ = 0.734, p < 0.01), with group communication explaining 53.9% of the variance in social concern (R² = 0.539). Both variables were rated ‘good’ overall (Variable X: grand mean = 3.35; Variable Y: grand mean = 3.34). These findings confirm that structured, norm-based, and goal-oriented group communication in value-based community organizations can serve as an effective instrument for fostering social concern.